Tinjauan Yuridis Penyelesaian Sengketa Atas Pemakai Kartu Kredit Tipe Gold Dengan Bank Penerbit Kartu Kredit (Studi Putusan No. 161/Pdt-G/2017/PN. Mdn) - Rahalim Raja Muda Harahap; Zaini Munawir; Sri Hidayani (Universitas Medan Area, 2019)
The credit card business in the modern era is now in great demand by the public so it is not surprising that banks are competing to issue credit cards with very attractive facilities that create competition between banks in Indonesia. This type of research is normative research, namely the type of research conducted by studying existing norms or legislation related to the issues discussed. The legal basis for credit card issuance is an agreement agreed by the parties, Act Number 3 of 2004 concerning Bank Indonesia. Law Number 10 of 1998 concerning National Banking. Decree of the Minister of Finance Number 1251 / KMK. 013/1988 Regarding the Provisions and Procedure for the Implementation of Bank Indonesia Regulation Financing Institutions Number 7/52 / PBI / 2005 concerning the Implementation of Card-Based Payment Instrument Activities, dated 28 December 2005, updated with Bank Indonesia Regulation Number 10/8 / PBI / 2008. Article 16 A and Article 16B of Bank Indonesia Regulation Number 14/2 / PBI / 2012. Factors that cause credit card disputes are delays and the inability to use credit cards to pay bills on their credit cards. Dispute Resolution in Decision No. 161 / Pdt.G / 2017 / PN. Mdn. Settlement is done through the Medan District Court because there is no settlement through consultation